Kepatuhan Indonesia Terhadap International Plan of Action on IUU FishingDalam Menangani Perikanan Ilegal di Perairannya - Gek Mahadewi, Ni Komang Ayu; Priadarsini, Ni Wayan Rainy; Widya Nugraha, A.A Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2018), 2018)
ABSTRACT This research was conducted by using qualitative research methods with the aim to be able to answer the research question related to how Indonesia complies with the International Plan of Action on Illegal, Unreported, Unregulated Fishing (IPOA-IUUF) regime in managing illegal fisheries in waters area. This research attempts to explain Indonesia's compliance with the international regime to deal with the problem of illegal fisheries. Although Indonesia's compliance with the rules of the IPOA-IUUF regime is carried out based on the calculation of profit and interest in handling with creating good fisheries governance for the country without IUU Fishing. The results of this research are description of the Indonesia's compliance with the IPOA-IUUF regime, the establishment of a national action plan in Ministerial Decree number 50 of 2012 is Indonesia's compliance. So, Indonesia is compliant with the IPOA-IUUF regime based on the existence of national, regional legislation and international active roles. Keyword: Indonesia, IUU Fishing, IPOA-IUUF regime, compliance